2000
DOI: 10.1002/1099-0739(200012)14:12<871::aid-aoc93>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

CO2-catalysed carbamation of aminofunctional silanes

Abstract: . These, upon reaction with dimethylcarbonate, are selectively converted into the methyl carbamate esters MeO(O) CNH(CH 2 ) Si(OMe) , MeO(O)CNH(CH 2 ) Si (OEt) and MeO(O)CNH(CH 2 ) 2 NH(CH 2 ) Si (OMe) respectively. Carbamate MeO(O)CNH (CH 2 ) Si(OEt) is accompanied by MeO(O)CNH (CH 2 ) Si(OMe) x (OEt)3 À x formed via transesterification of the triethoxysilyl group by the co-produced methanol. The carbamation process is very selective and N-methylated species are formed in trace amounts. Conversely, the ureido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 7 publications
0
87
0
1
Order By: Relevance
“…1 Carbon dioxide might also be utilized as an oxygen source or oxidant because it can be considered a nontraditional or mild oxidant and oxygen transfer agent. 2,3 It has been recently reported that carbon dioxide can be utilized as an oxidant for the oxidative conversions of alkanes, alkenes, and alcohols 4 and that oxygen generated during CO 2 reduction can participate in both partial oxidation and dehydrogenation. 4,5 Catalytic dehydrogenation of ethylbenzene (EB) is important in the manufacture of a styrene monomer (SM), which needs a large excess amount of superheated steam for preventing catalyst deactivation due to coke formation as well as enhancing catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Carbon dioxide might also be utilized as an oxygen source or oxidant because it can be considered a nontraditional or mild oxidant and oxygen transfer agent. 2,3 It has been recently reported that carbon dioxide can be utilized as an oxidant for the oxidative conversions of alkanes, alkenes, and alcohols 4 and that oxygen generated during CO 2 reduction can participate in both partial oxidation and dehydrogenation. 4,5 Catalytic dehydrogenation of ethylbenzene (EB) is important in the manufacture of a styrene monomer (SM), which needs a large excess amount of superheated steam for preventing catalyst deactivation due to coke formation as well as enhancing catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…7 Conversely, when unsaturated rhodium (I) complexes 'Rh(L-L)Cl' bearing a bidentate ligand (L-L = diphosphine, dipyridyl) are used, the mechanism of deactivation follows a different pathway. In this case, the coordinatively unsaturated 'Rh(L-L)Cl' moiety can be converted, by reaction with olefins, into a mixture of the penta-coordinated rhodium complex, Rh(L-L) 2 Cl, which no longer shows catalytic properties, 7 and Rh(olefin) n Cl, which is inactive. Owing to these facts, the life time of the catalyst rarely exceeds a few hours, with a serious limitation on the potential application in synthetic chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…142 Interestingly, CO 2 catalyzes reaction of aminosiloxanes H 2 NC 3 H 6 Si(OR) 3 with dimethylcarbonate to yield methyl carbamate esters. 144 The sol-gel hydrolytic condensation of such carbamates synthesized from mono-and diaminosiloxanes occurs without the decomposition of the carbamates. 145,146 Thermal treatment releases CO 2 to provide aminosilica materials retaining initial lamellar structure.…”
Section: Non-aqueous Solutions Of Amine Absorbentsmentioning
confidence: 99%